2020
DOI: 10.1007/s11207-020-01730-z
|View full text |Cite
|
Sign up to set email alerts
|

Solar Wind Plasma Particles Organized by the Flow Speed

Abstract: Recent reports of the first data from Parker Solar Probe (PSP) have pointed to a series of links, correlations or anti-correlations between the solar wind bulk speed ($V_{\mathrm{SW}}$ V SW ) and physical properties of plasma particles from less than 0.25 AU in the corona. In the present paper, we describe corresponding and additional links of solar wind properties, at 0.4 AU and 1.0 AU, in an attempt to complement the PSP data and understand their evolution. A detailed analysis is carried out for the main e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 45 publications
4
11
0
Order By: Relevance
“…Thus, low densities of the core corresponds to low values of κ: this indicates that high suprathermal tails for the halo are more present in low-density plasmas, when interactions between the particles, i.e., Coulomb collisions, are less frequent. The same conclusion is valid for the total number density, since it is close to the core density, as the ratio between halo and core density is always lower than 20% (Pierrard et al, 2020). This is quite logical since higher densities lead to VDF closer to Maxwellians, due to higher effects of Coulomb collisions, as shown in solar wind simulations based on the Fokker-Planck equation including Coulomb collisions (Pierrard et al, 2001b).…”
Section: Halo Temperature (T H ) Versus Kappa Exponent (κ)supporting
confidence: 58%
See 2 more Smart Citations
“…Thus, low densities of the core corresponds to low values of κ: this indicates that high suprathermal tails for the halo are more present in low-density plasmas, when interactions between the particles, i.e., Coulomb collisions, are less frequent. The same conclusion is valid for the total number density, since it is close to the core density, as the ratio between halo and core density is always lower than 20% (Pierrard et al, 2020). This is quite logical since higher densities lead to VDF closer to Maxwellians, due to higher effects of Coulomb collisions, as shown in solar wind simulations based on the Fokker-Planck equation including Coulomb collisions (Pierrard et al, 2001b).…”
Section: Halo Temperature (T H ) Versus Kappa Exponent (κ)supporting
confidence: 58%
“…at 0.4 AU (Pierrard et al, 2016). Pierrard et al (2020) had already shown that low halo density was associated to a higher bulk velocity. In the following, we study the interlinks between n h and other electron characteristics, first considering the core density n c .…”
Section: Influence Of the Halo Densitymentioning
confidence: 88%
See 1 more Smart Citation
“…It is primarily observed at energies above a breakpoint of about 50 eV at 1 au (green colour in Figure 1; McComas et al, 1992;Lie-Svendsen et al, 1997). The location of this breakpoint and the relative density of the halo population vary with distance from the Sun and show correlations with solar-wind parameters such as speed and temperature (Maksimovic et al, 2000(Maksimovic et al, , 2005Pierrard et al, 2016Pierrard et al, , 2020Bakrania et al, 2020). The halo population is often successfully modelled with a κ-distribution (using the Greek letter "kappa"; for detailed information about κ-distributions, see the recent textbooks by Livadiotis, 2017 and.…”
Section: Introductionmentioning
confidence: 97%
“…1; McComas et al, 1992;Lie-Svendsen et al, 1997). The location of this breakpoint and the relative density of the halo population vary with distance from the Sun and show correlations with solar-wind parameters such as speed and temperature (Maksimovic et al, 2000(Maksimovic et al, , 2005Pierrard et al, 2016Pierrard et al, , 2020Bakrania et al, 2020). The halo population is often successfully modelled with a κ-distribution (using the Greek letter "kappa"; for detailed information about κ-distributions, see the recent textbooks by Livadiotis, 2017 andFichtner, 2021).…”
Section: Introductionmentioning
confidence: 99%